2007
DOI: 10.1097/jom.0b013e318057777c
|View full text |Cite
|
Sign up to set email alerts
|

A 56-Year Mortality Follow-Up of Texas Petroleum Refinery and Chemical Employees, 1948–2003

Abstract: After more than half a century of follow-up, employees at this facility continue to show more favorable mortality outcomes than the general local population. Overall, no statistically significant increase of leukemia or of any of the specific cell types was found. The increased mesothelioma is likely related to past exposure to asbestos.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…Twenty-four cohort studies (Dement et al 2009a;Dement et al 2009b;Enterline et al 1987;Giaroli et al 1994;Harding et al 2009;Hein et al 2007;Hughes et al 1987;Krstev et al 2007;Levin et al 1998;Loomis et al 2009;Nokso-Koivisto and Pukkala 1994;Parnes 1990;Pira et al 2007Pira et al , 2009Puntoni et al 2001;Purdue et al 2006;Raffn et al 1989;Reid et al 2004;Sluis-Cremer et al 1992;Strand et al 2010;Tsai et al 2007;Ulvestad et al 2002Ulvestad et al , 2004Ward et al 1994) and a Finnish record linkage study (Tarvainen et al 2008) presented results on workers exposed to asbestos and cancers of the OC and/or pharynx. Among them, three referred to miners and millers (Pira et al 2009;Reid et al 2004;Sluis-Cremer et al 1992), six concerned workers of the construction industry (Dement et al 2009a, b;Krstev et al 2007;Puntoni et al 2001;Purdue et al 2006;Ulvestad et al 2004), three dealt with asbestos textile workers (Hein et al 2007;Loomis et al 2009;Pira et al 2007), and four concerned cement-asbestos workers (Giaroli et al 1994;Hughes et al 1987;Raffn et al 1989;…”
Section: Cohort Studiesmentioning
confidence: 96%
See 1 more Smart Citation
“…Twenty-four cohort studies (Dement et al 2009a;Dement et al 2009b;Enterline et al 1987;Giaroli et al 1994;Harding et al 2009;Hein et al 2007;Hughes et al 1987;Krstev et al 2007;Levin et al 1998;Loomis et al 2009;Nokso-Koivisto and Pukkala 1994;Parnes 1990;Pira et al 2007Pira et al , 2009Puntoni et al 2001;Purdue et al 2006;Raffn et al 1989;Reid et al 2004;Sluis-Cremer et al 1992;Strand et al 2010;Tsai et al 2007;Ulvestad et al 2002Ulvestad et al , 2004Ward et al 1994) and a Finnish record linkage study (Tarvainen et al 2008) presented results on workers exposed to asbestos and cancers of the OC and/or pharynx. Among them, three referred to miners and millers (Pira et al 2009;Reid et al 2004;Sluis-Cremer et al 1992), six concerned workers of the construction industry (Dement et al 2009a, b;Krstev et al 2007;Puntoni et al 2001;Purdue et al 2006;Ulvestad et al 2004), three dealt with asbestos textile workers (Hein et al 2007;Loomis et al 2009;Pira et al 2007), and four concerned cement-asbestos workers (Giaroli et al 1994;Hughes et al 1987;Raffn et al 1989;…”
Section: Cohort Studiesmentioning
confidence: 96%
“…Several studies assessed the risk of cancer of the OC and pharynx in various categories of workers exposed to asbestos, such as brake manufacturing workers (Parnes 1990), cable manufacturing workers (Ward et al 1994), insulation materials manufacturing workers (Levin et al 1998), locomotive drivers (Nokso-Koivisto and Pukkala 1994), various asbestos companies workers (Enterline et al 1987;Harding et al 2009), workers from various occupational groups exposed to different agents including asbestos (Strand et al 2010;Tarvainen et al 2008;Tsai et al 2007). Nonsignificantly (Enterline et al 1987;Harding et al 2009;Levin et al 1998;Parnes 1990;Strand et al 2010) or significantly (Nokso-Koivisto and Pukkala 1994;Ward et al 1994) increased risks were found in most of these studies.…”
Section: Cohort Studiesmentioning
confidence: 99%
“…Most were conducted in North America [7][8][9]11,[17][18][19][20][21]23,24,[28][29][30]32,33,37,39,40,42,44]; six in Scandinavia [25][26][27]36,38,41] and Europe [16,22,31,35,43,45]; and two in Australia/New Zealand [12,34]. Around half of the studies were interested in NHL incidence as the outcome [12,16,18,[25][26][27][33][34][35][36][37][38][39][40][41][42]…”
Section: Resultsmentioning
confidence: 99%
“…The majority studied workers employed in refineries and petrochemical plants [7][8][9]11,[16][17][18][19][20][21][22][23]25,26,[28][29][30]32,36,37,42], land-or marine-based distribution centres [11,16,24,26] or in the downstream petroleum industry in general [12,[43][44][45]. Some reported risks for motor mechanics [34,36,41] or filling station attendants [27,31,36], while the remainder only asked subjects whether they were exposed to gasoline at work [33,35,[38][39][40].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation